Temperature and Photoperiod Influence Trichome Density and Sesquiterpene Content of Lycopersicon hirsutum f. hirsutum - Gianfagna, Thomas J. (1992)
Resistance to Colorado potato beetle in a clone of Lycopersicon hirsutum f. hirsutum L. is attributed to the presence of the sesquiterpene zingiberene in the type VI leaf trichomes; however, both day/night temperature regimen and photoperiod affect zingiberene content and trichome density. In short days (SD), zingiberene content per trichome is more than 3-fold greater than in long days. In SD, trichome density per unit leaf surface is 2-fold greater at 25/20°C (day/night) than at either 30/25°C or 20/15°C, thus indirectly influencing zingiberene content per cm(2). In long days, temperature regimen had little effect on either trichome density or zingiberene content, although trichome density was greater than or equal to that in SD.